Sociodemographic determinants of depression, anxiety, and stress immediately after the COVID-19 pandemic: a cross-sectional study among university students in Saudi Arabia - Alasqah, Ibrahim; Alhamdan, Abdullah; Alhouri, Mohammad; Alfehaid, Mohammed (Frontiers in Public Health, 2024)
The public health measures taken in educational institutions during the COVID-19 pandemic had complex influences on students' mental health. This study aimed to evaluate the prevalence and socio-demographic determinants of Depression, Anxiety, and Stress immediately after the COVID-19 pandemic among students at Qassim University, Saudi Arabia. Methods: We conducted a cross-sectional study among Qassim University students in Saudi Arabia. All students registered for the academic year 2022 were invited to participate in a survey through social media. A total of 453 participants completed an online survey that included the DASS-21 scale for assessing the emotional states of Stress, Anxiety, and Depression. Results: The mean scores for Stress, Anxiety, and Depression were 10.40, 11.18, and 10.70, respectively. At least 18% of the students reported experiencing moderate to severe levels of Stress, Anxiety, and Depression. The study showed that female gender and studying in higher academic years werewas associated with higher Stress, Anxiety, and Depression scores. Conclusions: Students in the current study described experiencing high levels of Stress, Anxiety, and Depression during the COVID-19 pandemic. The findings of the present study can help universities take targeted measures to address the impact of a pandemic like COVID-19 on students' mental health.